PENERAPAN KONSEP “AKU CINTA PRODUK INDONESIA” MENGGUNAKAN MEDIA SOSIAL UNTUK MEMBANGUN LOYALITAS (STUDI KASUS TWITTER JOMBANG KULINER ) (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2015)
Asean economic community is not merely a conjecture, yet it is going to be carried out at the end of 2015. How to build up customer' loyalty to any domestic products is the most essential thing to prepare. It is hoped that the loyalty can be one of the competitive advantages to Indonesian products in facing foreign surge. Nowadays, many ways are used to strengthen loyalty, one of them is social media. Creating customer relation through technology communication is the most effective method to endorse customer loyalty. Based on the elaboration above, this research is aimed to know the influence of satisfaction with website to customer loyalty through the variables of satisfaction with vendor. The purposive sampling technique spread via e-mail to 100 twitter member of Jombang Kulineris used. This research is positivist research method which use path analysis technique. This research proved that the influence of satisfaction with website to customer loyalty through the variables of satisfaction with vendor. Unfortunately, the direct effect of satisfaction with website on customer loyalty did not prove.